Rhetorical moves analysis in instagram advertisements written by women entrepreneurs - Amizan Azim Ramli,; Norizan Abdul Razak, (Penerbit Universiti Kebangsaan Malaysia, 2023)
In the rapidly evolving digital economy, social media has emerged as a crucial tool for small and medium-sized enterprises (SMEs) to promote their products and services. In Malaysia, where English serves as a lingua franca for intercultural communication and business activities, English language skills are essential for non-native English-speaking SMEs to conduct business at the international level. However, there is limited research on how Malaysian SMEs write effective online advertising strategies, especially in social media. The present challenges for SMEs who may struggle with language barriers further compound this situation. To address this, this study employs genre analysis to investigate the rhetorical moves employed by women entrepreneurs in Malaysia in their online advertisements on Instagram. 15 Instagram accounts of female bakery entrepreneurs were studied. They effectively employed hashtags and call-to-action approaches in their marketing, aligning with past research on engaging consumers through social media advertisements. This study contributes to the literature on social media advertising by providing insights into the rhetorical strategies used by women entrepreneurs in Malaysia. It highlights the significance of understanding the language and cultural context in which SMEs operate to develop effective marketing communication strategies. Moreover, this study also contributes to the literature on genre theory by showcasing how it can be applied to analyze digital advertising genres. Moving forward, our findings underscore the practical implications of comprehending and harnessing these rhetorical strategies, offering a compass for SMEs to navigate the dynamic landscape of contemporary business promotion in the digital era. This study also advances genre theory by applying it to analyze digital advertising genres. The findings offer practical insights for SMEs to adeptly navigate the evolving digital business landscape.